The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jcd.21326
|View full text |Cite
|
Sign up to set email alerts
|

Defining Sets and Critical Sets in (0,1)‐Matrices

Abstract: If D is a partially filled‐in (0, 1)‐matrix with a unique completion to a (0, 1)‐matrix M (with prescribed row and column sums), we say that D is a defining set for M. If the removal of any entry of D destroys this property (i.e. at least two completions become possible), we say that D is a critical set for M. In this note, we show that the complement of a critical set for a (0, 1)‐matrix M is a defining set for M. We also study the possible sizes (number of filled‐in cells) of defining sets for square matrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Observe that any (0, 1)-matrix m × n is in fact a subset of F m,n . Indeed, any trade in a (0, 1)-matrix is a disjoint union of trade cycles ( [3]; an equivalent result is also shown by Lemma 3.2.1 of [2]). …”
Section: A Classification Of Critical Setsmentioning
confidence: 89%
See 1 more Smart Citation
“…Observe that any (0, 1)-matrix m × n is in fact a subset of F m,n . Indeed, any trade in a (0, 1)-matrix is a disjoint union of trade cycles ( [3]; an equivalent result is also shown by Lemma 3.2.1 of [2]). …”
Section: A Classification Of Critical Setsmentioning
confidence: 89%
“…This is useful because it is well-known that a (0, 1)-matrix has no trades (and is thus the unique member of its class A(R, S)) if and only if its rows and columns can be rearranged so that a line of non-increasing gradient can be drawn with all the 0's below and the 1's above. This statement of the Gale-Ryser theorem (see [2]) is given as Lemma 3 in [3].…”
mentioning
confidence: 99%
“…With R and S as above, we next define A R S ′( , ) to be the set of all m n × ⋆ (0, 1, )-matrices with 1. at most r i 1's in row i, 2. at most n r − i 0's in row i, 3. at most s j 1's in column j, 4.…”
mentioning
confidence: 99%
“…Precise bounds for scs(Λ ) n x were obtained in [6] for small values of x and upper bounds for general x, including scs ≤ m (Λ ) m m 2 2 . In [3], it is shown that ≥ x n x scs(Λ ) min{ , ( − ) } n x 2 2 , a corollary of which is:…”
mentioning
confidence: 99%
“…{ , }-matrices are closely related to graph theory and combinatorial mathematics [1][2][3][4]. They also have a wide range of practical applications in statistics and probability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%